Decision-making processes of weaning from mechanical ventilation: a comparative ethnographic insight into the dynamics of the decision-making environment - Kydonaki, Kalliopi (The University of Edinburgh, 2011)
Many critical clinical conditions result in respiratory failure and precipitate the use of mechanical ventilation for their management. A prolonged period of mechanical ventilation is costly for both the patient, in terms of adverse effects, and the health care service. Therefore, immediate liberation of the patient from mechanical ventilation and constitution of spontaneous breathing, a process called weaning, is vital. This daily lifesaving practice, on which nurses are taking an increasing role with the introduction of nurse-led protocols, can become complicated requiring the effective use of assessment information through decision-making processes to improve outcomes of care. Most literature on the field fails to address that weaning decisions are affected not only by the nature of the task but also by the characteristics of the decision-maker and the decision environment. This research aimed to study nurses' decision-making processes when managing the weaning of long-term ventilated patients and to explore the impact of the diverse elements of the clinical environment on this intricate practice. An ethnographic approach was used to compare weaning decision-making processes in two different culturally intensive care units (ICU). Participant observation was used to follow the weaning practices of 10 patients in a Scottish ICU and 9 patients in a Greek ICU admitted with respiratory failure due to pneumonia or COPD exacerbation. Nurses were observed in their daily weaning practice and participated in reflective interviews at the end of their shift to extrapolate how they used the information to make their decisions. Semi-structured interviews were, then, conducted with nurses, physiotherapists and medical staff to explore their perceptions on weaning practices and the factors that influenced their decisions and clinical practice. Data were analysed thematically and concept maps were developed from the reflective interviews to analyse nurses‟ decision-making processes. The concept attainment theory was used as a framework to understand nurses' thinking processes. Nurses in all ranges of experience demonstrated a similar decision-making skill, which signifies that this cognitive process is not always related to the level of experience and knowledge. Nurses' weaning care was organised around maintaining a balance of care under the 'wean as able' medical instruction. Inconsistency in the weaning decisions led to a variability of weaning approaches followed for each patient and to long periods of weaning inactivity. Various reasons, related to the working relationships, lack of nurses‟ accountability, lack of support and unstructured information flow, were responsible for the deficiency in sustainable and consistent weaning decisions. In both settings, there was lack of culture to foster a shared decision-making approach in weaning practice and encourage nurses' autonomy in decision-making. This study concluded with proposing a collaborative decision-making framework for weaning long-term ventilated patients, which will involve and appreciate the contribution of all members of the multidisciplinary team.
Keywords: weaning mechanical ventilation; decision-making